2013
DOI: 10.1183/20734735.006513
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant in newborn infants and children

Abstract: N To understand the composition, secretory pathways and functions of pulmonary surfactant.N To review the clinical evidence regarding the use of surfactants in newborn infants and children.N To develop an understanding of rarer disorders of surfactant metabolism. N To understand recent developments and future prospects in the field of surfactants. SummaryPulmonary surfactant is a complex mixture of specific lipids, proteins and carbohydrates, which is produced in the lungs by type II alveolar epithelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 84 publications
(88 reference statements)
0
39
0
3
Order By: Relevance
“…Based on these findings, it was concluded that caffeine may not only accomplish the supply of the body tissues with adequate O 2 via the devices, but also prevent any inconvenience for the infants undergoing endotracheal intubation and mechanical ventilation. Premature infants are at high risk of developing breathing problems, as their lungs do not produce sufficient amounts of surfactants, which keep the lung alveoli open (34). Therefore, selecting a method of supplemental O 2 delivery should be carefully considered, since in certain cases the artificial breathing machine may result in lung problems, such as BPD (35).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it was concluded that caffeine may not only accomplish the supply of the body tissues with adequate O 2 via the devices, but also prevent any inconvenience for the infants undergoing endotracheal intubation and mechanical ventilation. Premature infants are at high risk of developing breathing problems, as their lungs do not produce sufficient amounts of surfactants, which keep the lung alveoli open (34). Therefore, selecting a method of supplemental O 2 delivery should be carefully considered, since in certain cases the artificial breathing machine may result in lung problems, such as BPD (35).…”
Section: Discussionmentioning
confidence: 99%
“…Высока вероятность связи SP-C с жидким бислоем дипальмитоилфосфатидилхолина. Кроме того, SP-C может вклиниваться в двухслойный фосфолипид, поддерживая монослой поверхностно-активного вещества в альвеоле, усиливать поглощение и катаболизм фосфолипидов альвеолоцитами II типа [3,4,30]. SP-B и SP-C синтезируются в клетках альвеолярного типа II в виде больших белков-предшественников (proSP-B и proSP-C) в эндоплазматическом ретикулуме, которые расщепляются протеолитическими ферментами с получением меньших, чрезвычайно гидрофобных пептидов (рис.…”
Section: современное представление о роли мутаций протеинов сурфактанunclassified
“…Лизосома сливается с ламеллярной гранулой, зрелые белки встраиваются в поверхностно-активные фосфолипидные мембраны, и происходит секреция путем слияния мембраны ламеллярной гранулы с плазматической мембраной эпителиальной клетки, в результате чего содержимое выливается в альвеолярное пространство [26]. Богатое фосфолипидом содержимое собирается в трубчатый миелин, который служит резервуаром поверхностноактивного вещества во время дыхания и усиливает выведение липидов в альвеолярное пространство [30].…”
Section: современное представление о роли мутаций протеинов сурфактанunclassified
See 1 more Smart Citation
“…Each of these structures is made of multiple specialized epithelial cell types that help carry out the lung’s unique functions of air intake and gas exchange, epithelial barrier function, protection from microbes and pathogens, and the maintenance of fluid and electrolyte homeostasis. [ 1 ] The diverse repertoire of respiratory epithelial cells that comprise the trachea, airways, and alveoli are derived from a common population of progenitor cells that are specified in the endodermal germ layer early during development. [ 2 4 ] In addition to the endoderm-derived epithelium, both the developing and mature respiratory systems contain cells derived from the mesoderm (e.g., smooth muscle) and ectoderm (e.g., neurons) germ layers, and the complex interactions between cells from all three germ layers are absolutely critical for proper respiratory system development and function.…”
Section: Introductionmentioning
confidence: 99%